The Association of Grip Strength with Depressive Symptoms Among Middle-Aged and Older Adults with Different Chronic Diseases - De Moraes-Ferrari, G (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Low grip strength has been associated with an increase in depressive symptoms, independent of age group or gender, although the literature has not investigated this association among different chronic diseases. The present study aims to investigate the association of grip strength and depressive symptoms among middle-aged and older adults with different chronic diseases. A cross-section of data from the Survey of Health, Ageing, and Retirement in Europe wave 6 (collected in 2015) was analysed. Grip strength was measured by a handgrip dynamometer, and the European Depression Symptoms 12-item scale (EURO-D) was used to assess depressive symptoms. Multivariable logistic regression analysis was conducted. Those in the high strength tertile had 42% (95% confidence interval: 0.50, 0.71; p < 0.005) and 41% (95% confidence interval: 0.50, 0.70; p < 0.001) lower odds of depressive symptoms in the ‘no disease’ and in the ‘metabolic diseases’ groups of participants, respectively, compared with those in the lower strength tertile. No statistically significant relationship between grip strength and depression was observed in the ‘arthritis diseases’ group of participants. The association of grip strength with depressive symptoms must consider, besides gender and age group, the chronic conditions that an individual could have. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.